Licneremaeus licnophorus - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Licneremaeus licnophorus (Michael, 1882) Material – One specimen in Karadedeoğlu Village Tekkeyaylası Area, Taşköprü forest, N 41° 22′ 24.45′′, E 34° 23′ 25.15′′, alt. = 1224 m, 2 August 2018, tree trunk of P. nigra; one specimen in Karadedeoğlu Village, Taşköprü forest, N 41° 22′ 55.11′′, E 34° 24′ 03.56′′, alt. = 1201 m, 17 July 2018, tree bark and debris of P. nigra. Previous record in Turkey – Bolu (Toluk and Ayyildiz 2011). Global distribution – Holarctic. Ecology – Moss, tree trunks.

Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 263, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444
Keywords: Arthropoda; Arachnida; Licneremaeus; Animalia; Biodiversity; Sarcoptiformes; Licneremaeus licnophorus; Taxonomy; Licneremaeidae; 15. Life on land